Cognitive energy of the figurative word in modern scientific discourse - Голованова, Елена Иосифовна (Philological Studies: the Scientific Publication of Kryvyi Rih State Pedagogical University, 2014)
In the article the features of figurative statement of facts in the scientific discourse. The author argues that the new knowledge when making images enhance mental activity of the reader, serve as a means of persuasion, an instrument precise specifications and interpretation.